Protective effects of fecal microbiota transplantation against ischemic stroke and other neurological disorders: an update - Hediyal, Tousif Ahmed; Vichitra, C.; Anand, Nikhilesh; Bhaskaran, Mahendran; Essa, Saeefh M.; Kumar, Pravir; Qoronfleh, M. Walid; Akbar, Mohammed; Kaul-Ghanekar, Ruchika; Mahalakshmi, Arehally M.; Yang, Jian; Song, Byoung-Joon; et al. (Frontiers in Immunology, 2024)
The bidirectional communication between the gut and brain or gut-brain axis is regulated by several gut microbes and microbial derived metabolites, such as short-chain fatty acids, trimethylamine N-oxide, and lipopolysaccharides. The Gut microbiota (GM) produce neuroactives, specifically neurotransmitters that modulates local and central neuronal brain functions. An imbalance between intestinal commensals and pathobionts leads to a disruption in the gut microbiota or dysbiosis, which affects intestinal barrier integrity and gut-immune and neuroimmune systems. Currently, fecal microbiota transplantation (FMT) is recommended for the treatment of recurrent Clostridioides difficile infection. FMT elicits its action by ameliorating inflammatory responses through the restoration of microbial composition and functionality. Thus, FMT may be a potential therapeutic option in suppressing neuroinflammation in post-stroke conditions and other neurological disorders involving the neuroimmune axis. Specifically, FMT protects against ischemic injury by decreasing IL-17, IFN-γ, Bax, and increasing Bcl-2 expression. Interestingly, FMT improves cognition by lowering amyloid-β accumulation and upregulating synaptic marker (PSD-95, synapsin-1) expression in Alzheimer’s disease. In Parkinson’s disease, FMT was shown to inhibit the expression of TLR4 and NF-κB. In this review article, we have summarised the potential sources and methods of administration of FMT and its impact on neuroimmune functions. We also provide a comprehensive update on the beneficial effects of FMT in various neurological disorders by undertaking a detailed interrogation of the preclinical and clinical published literature.